2019
DOI: 10.1002/ange.201903841
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Primary Anilines from NH3 and Cyclohexanones by Utilizing Preferential Adsorption of Styrene on the Pd Nanoparticle Surface

Abstract: Dehydrogenative aromatization is one of the attractive alternative methods for directly synthesizing primary anilines from NH 3 and cyclohexanones.However,the selective synthesis of primary anilines is quite difficult because the desired primary aniline products and the cyclohexanone substrates readily undergo condensation affording the corresponding imines (i.e., N-cyclohexylidene-anilines), followed by hydrogenation to produce N-cyclohexylanilines as the major products.Inthis study,primary anilines were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This result indicated that the side product 5 aa was generated through hydrogen transfer, that is, the imine intermediate was reduced by the Pd−H species formed through the dehydrogenation of another imine . It was hypothesized that this problem could be mitigated through the use of oxidants or hydrogen scavengers, and the corresponding screening (Figure b, entries 6–8) revealed that styrene (2 equiv) acted as a good hydrogen scavenger to achieve excellent product selectivity. Under optimal reaction conditions [column reactor diameter=10 mm, length=10 cm; catalyst=mixture of Pd(OH) 2 /C and Celite ® (1:10 w/w, ≈4.9 g)], the desired diaryl amine 4 aa could be continuously produced as the sole product in excellent yield for at least 24 hours (Figure b, entry 8).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This result indicated that the side product 5 aa was generated through hydrogen transfer, that is, the imine intermediate was reduced by the Pd−H species formed through the dehydrogenation of another imine . It was hypothesized that this problem could be mitigated through the use of oxidants or hydrogen scavengers, and the corresponding screening (Figure b, entries 6–8) revealed that styrene (2 equiv) acted as a good hydrogen scavenger to achieve excellent product selectivity. Under optimal reaction conditions [column reactor diameter=10 mm, length=10 cm; catalyst=mixture of Pd(OH) 2 /C and Celite ® (1:10 w/w, ≈4.9 g)], the desired diaryl amine 4 aa could be continuously produced as the sole product in excellent yield for at least 24 hours (Figure b, entry 8).…”
Section: Figurementioning
confidence: 99%
“…Thus, consecutive condensation and dehydrogenation would proceed smoothly to afford the desired aryl amines without any by‐products because of the absence of hydrogen. Furthermore, division of the flow reactors would enable the use of a hydrogen scavenger in the second stage to more reliably control product selectivity. This segmentation and integration strategy could significantly improve the amine scope and product selectivity, while some features of flow reactors loaded with heterogeneous catalysts could not only increase reaction efficiency, but also allow reaction conditions milder than those used in the corresponding batch reactions to realize the continuous synthesis of various aryl amines …”
Section: Figurementioning
confidence: 99%